Variables That Influence the Digital Competence Achievement Level (Dcal) of University Students; [Variables Que Influyen en el Grado de Logro de la Competencia Digital (Glcd) de Estudiantes Universitarios] - Silva-Quiroz, J (Centro de Informacion Tecnologica, 2024)
The objective of this study is to describe and analyze the context variables of significant incidence on the level of achievement of digital competence (GLCD) of students at a Chilean public university. University students are users of digital technologies, but they do not use them to favor their academic training. The methodology is descriptive and inferential non-experimental. An instrument based on the DIGCOMP framework is applied to a sample of 2441 students. The results show that in the areas of “digital information and alphabetization” and “online security,” females present significantly higher scores than men, while the opposite is obtained on “digital content creation.” It is concluded that it is necessary to assess the development of digital competence (DC) and the variables that affect it in order to generate effective strategies to improve student achievement levels. © (2024), (Centro de Informacion Tecnologica). All Rights Reserved.